Playgroup participation in the Longitudinal Study of Indigenous Children (LSIC) families: Engagement and outcomes - Williams, Kate; Viviani, Maria; Berthelsen, Donna; Nicholson, Jan M (My University, 2015)
Across Australia, national and state policy initiatives support playgroup participation for families with young children. Playgroups are gatherings of parents and young children together in weekly play sessions, some with a paid facilitator and some without. They are designed to support children’s early learning and improve social connections for parents. Very limited evidence as to their effectiveness in meeting these aims exists. This study uses data from the Longitudinal Study of Indigenous Children (LSIC) to describe patterns of playgroup attendance over time and associations with child, parent, and community outcomes for Aboriginal and Torres Strait Islander families. The analysis involved 839 children and their parents from the Baby Cohort of LSIC and utilised data from three waves of data collection, when children were 2, 3, and 4 years of age. 11% of children had attended playgroup at both 2 and 3 years of age; 23 % had attended playgroup at either 2 or 3 years of age; and 66% had not attended playgroup at either age. A range of child, parent, and community level outcomes were examined with level of playgroup attendance most strongly associated with increased parental engagement in book reading and increased advice-seeking. While current evidence on the value of supported playgroups remains relatively limited, this study provides important findings that playgroup participation can provide support for Aboriginal and Torres Strait Islander families particularly in relation to home learning environments and social support.
Keywords: Children -- School age; Children -- Early childhood; Families,Adolescents and Youth -- Parents and Parenting; Actvities -- Children's activities; Adolescents and youth; Childhood and child development; Families and relationships; Actvities; Children; Families,Adolescents and Youth; Parents and Parenting; School age; Early childhood; Children's activities; Families and relationships; Adolescents and youth; Childhood and child development